Comparative Study of C++ and C# Programming Languages - Veny Vita Ponggawa; Utari B. Santoso; Gita A. Talib; March A. Lamia; Ariel R.A Manuputty; Muhammad F. Yusuf (Jurnal Syntax Admiration, 2024)
This comparative study explores the similarities and differences between two widely-used programming languages: C++ and C#. While both languages are integral to modern software development, they cater to different development environments and paradigms. C++, a general-purpose programming language, is known for its performance efficiency and low-level memory management, making it ideal for system software, embedded systems, and performance-critical applications. In contrast, C#, a high-level language developed by Microsoft, is primarily used in the .NET ecosystem for building Windows applications, web services, and enterprise solutions. This study examines various aspects of both languages, including syntax, memory management, performance, ease of use, and application domains. By analyzing these parameters, the paper aims to provide a comprehensive comparison that highlights the strengths and weaknesses of C++ and C# in different programming contexts. Additionally, the study discusses the role of both languages in modern development environments and their suitability for various types of projects. The findings suggest that while C++ remains the preferred choice for performance-sensitive applications, C# offers a more user-friendly environment for rapid application development, particularly in enterprise and web-based applications.